Using the Lecture Method of teaching and learning Activities about Lao grammar for primary section students - SORPHIMPHA, Phonchan (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This research aimed: to study the effectiveness of lesson plans for using lecture Method and, to compare before and after the results of learning about Lao grammar for using Lecture Method. The samples were primary students. There are 28 participants, including 15 female participants, who have been learning at the primary education section, system 12+4 in the first term of academic year 2017-2018. The learning and teaching period was 24 hours. The instruments for research were: 1) a lesson plans, 2) an achievement test. Data analysis was using by mean (), standard Deviation (S.D), and data analysis E1/E2 and (T-test). The research has two results of data analysis as following: - The effectiveness of Lao grammar was using Lecture method equal 81,11/82,94 high than data analysis manipulation 80/80. - The result of learning Lao grammar before and after teaching the result of how to used Lecture Method are differences, the result of learning after was (=37,32, S.D=3,09) high than the result before learning (=22,34, S.D=2,99) considered the result of standard used 0,05.